MiR‐148b inhibits glycolysis in gastric cancer through targeting SLC2A1. (24th April 2017) - Ding, Xiangfu; Liu, Jingjing; Liu, Tianzhou; Ma, Zhiming; Wen, Dacheng; Zhu, Jiaming
Abstract: Although the molecular biology of GC has been well characterized, early diagnostic biomarkers and effective therapeutic options in gastric cancer are still under investigation. Here, we found that miR‐148b expression decreased in human gastric cancer tissues compared with matched adjacent nontumor tissues by q‐PCR analysis and in situ hybridization. Further investigation revealed that overexpression of miR‐148b limited glycolysis including glucose consumption, lactate production in gastric cancer cell lines BGC‐823 and MKN45. Bioinformatics prediction uncovered that a dedicated transporters solute carrier family 2 member 1 (SLC2A1), also called GLUT1, was the direct target of miR‐148b. The target effects were further confirmed by luciferase assay and western blot analysis. Besides, a reverse correlation was observed between relative SLC2A1 and miR‐148b expression in human GC tissues compared with matched adjacent nontumor tissues. Subsequently, SLC2A1 suppression by SLC2A1 siRNA or specific inhibitor restricted the reduced effects of glycolysis mediated by miR‐148b while SLC2A1 overexpression abrogated the effect of miR‐148b on glycolysis. Our findings provided new evidence of miR‐148b in GC development through restraining glycolysis, highlighting the role of miR‐148b as a new target for GC treatment. Abstract : miR‐148b inhibits GC development through restraining glycolysis, highlighting the role of miR‐148b as a new target for GC treatment.